SOSIALISASI 5 M SEBGAI UPAYA PENCEGAHAN PENYEBARAN COVID-19 BAGI IBU HAMIL DI BP MUSLIMAT DESA SELOREJO KABUPATEN JOMBANG - Ferilia Adiesti; Nurun Ayati Khasanah; Sulisdiana; Fitria Edni Wari; Citra Adityarini Safitri (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2021)
COVID-19 is a pandemic that is occurring in many countries around the world. Indonesia is one of the countries affected by this virus outbreak. COVID-19 can spread mainly from person to person through droplets from the nose or mouth that come out when a person infected with COVID-19 coughs, sneezes or talks. Efforts made to prevent the transmission of the COVID-19 outbreak in pregnant women are: keep doing 5m, namely: wearing masks, washing hands with soap, maintaining distance, avoiding crowds and reducing mobility. Some people are still neglecting to do 5M during the current pandemic, this happens because of the lack of public knowledge about the COVID-19 health protocol. Therefore, the COVID-19 Health Protocol Discipline Counseling is carried out so that the community has a high level of awareness and concern for the dangers. COVID-19 transmission. This community service activity was carried out by Selorejo Village with 5M counselling through a structured implementation approach. The result achieved from this outreach activity is that public knowledge increases about the discipline of COVID-19 health protocols